2021
DOI: 10.1111/syen.12512
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Nabidae (Hemiptera: Heteroptera: Cimicomorpha): insight into relationships and reclassification with the proposal of the new tribe Stenonabini

Abstract: Nabidae is a small predatory family within Cimicomorpha; however, the internal classification within this family has been unclear and controversial, confusing researchers in various fields. This study presents the first comprehensive phylogenetic analysis of Nabidae based on a molecular dataset comprising 16 outgroup and 40 ingroup taxa. A total of 3791 base pairs of mitochondrial (16S, cytochrome oxidase subunit I) and nuclear (18S, 28S) sequences were analyzed based on parsimony, maximum likelihood and Bayes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
3
1
Order By: Relevance
“…Compared to other recent phylogenetic studies, our results do not support the hypothesized sister-group relationships of Xylocorini + Cimicidae + Plokiophilidae [ 3 ], Lyctocoridae + Oriini [ 2 ], and Lyctocoridae + (Plokiophilidae + Oriini) + (Cimicidae + Anthocorini) [ 59 ] because Oriini was clustered with Cardiastethini (except for Amphiareus ) in all analyses ( Figure 3 ; Figure S1 ). Additionally, all analyses did not support that Lasiochilidae is a sister group to all remaining cimicoids ( Figure 3 , Figures S1 and S2 ), in disagreement with the findings of previous phylogenetic studies [ 2 , 3 , 6 , 7 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Compared to other recent phylogenetic studies, our results do not support the hypothesized sister-group relationships of Xylocorini + Cimicidae + Plokiophilidae [ 3 ], Lyctocoridae + Oriini [ 2 ], and Lyctocoridae + (Plokiophilidae + Oriini) + (Cimicidae + Anthocorini) [ 59 ] because Oriini was clustered with Cardiastethini (except for Amphiareus ) in all analyses ( Figure 3 ; Figure S1 ). Additionally, all analyses did not support that Lasiochilidae is a sister group to all remaining cimicoids ( Figure 3 , Figures S1 and S2 ), in disagreement with the findings of previous phylogenetic studies [ 2 , 3 , 6 , 7 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The model-based analyses indicated that Plokiophilidae is the sister group to all remaining groups within Cimicoidea ( Figure 3 ). This is congruent with the results from model-based analyses in Kim et al (2022) [ 59 ] but is incongruent with the results from the preferred topology within Cimicomorpha in Schuh et al (2009) [ 2 ], and the results from the previous study in Jung et al (2010) [ 3 ], respectively.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Important morphological characters to identify Nabidae include the moderate size of the body (rarely exceeding 10 mm), elongated head, labium flexible and usually curving, 4 segmented labium and antenna, antennal prepedicellite present, In most species, fossula spongiosa in protibiae and mesotibiae is present (Panizzi, 2015). This family currently includes 20 genera and 500 species (Faúndez & Carvajal, 2014), classified into two subfamilies, Nabinae A.Costa, 1853 and Prostemmatinae Reuter, 1890 (Kim et al, 2021). Prostemmatinae is a relatively small group, which has five genera with approximately 150 described species worldwide (Schuh & Slater, 1995;Cassis, 2016), in the Palaearctic region, 4 genera and approximately 30 species were reported (Lee et al 2019).…”
Section: Introductionmentioning
confidence: 99%